Perceptions and Practices of Nurses with Respect to Asylum-Seekers and Refugees Accessing Health Care Services In Musina, Limpopo, South Africa - Ndemere, Taurai (Department of Public Health and Family Medicine, 2021)
To achieve the goal of universal health coverage, no one should be left behind. To achieve this goal, refugees and asylum seekers should be prioritised due to their heightened risks. This would improve health outcomes and assist in attaining the Sustainable Development Goals (SDGs) of 2030. In the South African context, numerous studies have been conducted on access to health care services from asylumseekers and refugees' perspectives. It is a complicated problem, however, both the service providers' point of view and that of the patient need to be explored and understood deeply for effective action to be taken. A lack of studies from the service providers (professional and enrolled nurses) lens on asylumseekers and refugees accessing healthcare services, specifically in Musina, Limpopo, South Africa, motivated this study. The study aimed at providing more information on the perceptions and practices of nurses on asylum-seekers and refugees accessing health care services. A qualitative approach was utilised to explore the perceptions and practices of nurses with regards to asylum-seekers and refugees accessing healthcare services. The study was conducted at Nancefield clinic and the Musina hospital in Musina with professional nurses. Semi-structured interviews were utilised to collect data and a thematic analysis approach was utilised to analyse the data. The study provided some insight on the perceptions and practices of healthcare providers. Due to the small sample size, it cannot be concluded that there is no systematic discrimination of asylum-seekers and refugees in South Africa. Nurses were incorrectly classifying asylum-seekers and refugees as economic migrants. Most nurses were of the view that the majority of their patients were migrants, including asylum-seekers and refugees. Nurses said that they apply the law in their practices as expected. Nurses believe in work documents and the hierarchy of power. These two factors guide nurses when interacting with asylum-seekers and refugees accessing their services. The study recommends that stakeholders that are working with refugees and asylum-seekers conduct capacity-building activities with nurses to raise awareness on the relationship between migration and health or government requests training.